STRUCTURAL ORGANIZATION OF AGGRESSIVENESS IN ADOLESCENTS WITH DIFFERENT LEVELS OF «END-NON-IMPRESSURE» AND «END-UNY» - G. Uvarova; N. Shevkiyeva (Вестник университета)
The research of the structural organization of the components of aggressiveness in adolescents with different levels of envy-dislike and envy-despondency has been conducted. With the assistance of structural-psychological analysis, it has established that the structures of aggressiveness in adolescents with medium and high levels of envy-despondency are heterogeneous, that is, qualitatively differing in weight of elements in the compared structures. The structure of aggressiveness in adolescents with an average level of envy-despondency is more consistent, in adolescents with a high level of envy-despondency, on the contrary, the degree of functioning of the structure of aggressiveness is lower, that is the latter it is more independent.